Exploring the SEW effectiveness in family firms resilience. Insights from the pandemic - Capolupo, Nicola (Piccola Impresa / Small Business, 2023)
Purpose: This paper explores the impact of Socioemotional Wealth (SEW) on family firms’ resilience during the Covid-19 pandemic. Design/Methodology/Approach: Through a multiple case study analysis, constructs drafted from the literature were associated with each of the FIBER approach dimensions and investigated through open-ended interviews with two family firm managers. Findings: Results revealed which dimensions of this approach proved to be most relevant, and by which conditions they were influenced.